The relationship between social supports and psychological problems among students - Md Yasin, Md Aris Safree; Dzulkifli, Mariam Adawiah (Center for Promoting Ideas (CPI), 2010)
This study was conducted to examine the relationship between social support and psychological problems i.e. depression, anxiety, and stress. 120 undergraduate university students were involved in this study. They were selected using purposive sampling technique. The Social Support Behaviour (SSB) scale was used to measure the level of social support among students and the Depression Anxiety Stress Scale (DASS) was used to measure the level of depression, anxiety, and stress among students. Correlation coefficient was used to measure the relationship between social support and psychological problems. The findings of this study revealed that there were significant negative relationship between social support and psychological problems suggesting that the higher the social support, the lower is the psychological problem. The findings of the study will be useful in assisting educators, counsellors, psychologist, and researchers to develop strategies to enhance student psychological well-being.